2001
DOI: 10.2307/2680102
|View full text |Cite
|
Sign up to set email alerts
|

Colonization Success in Roesel's Bush-Cricket Metrioptera roeseli: The Effects of Propagule Size

Abstract: Assessing the colonizing ability of a species is important for predicting its future distribution or for planning the introduction or reintroduction of that species for conservation purposes. The best way to assess colonizing ability is by making experimental introductions of the species and monitoring the outcome. In this study, different-sized propagules of Roesel's bush-cricket, Metrioptera roeseli, were experimentally introduced into 70 habitat islands, previously uninhabited by the species, in farmland fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 28 publications
4
66
1
Order By: Relevance
“…A low probability of establishment when population size is small is consistent with the low success rate in establishing biocontrol agents (Grevstad 1999, Stiling 1990, Shea and Possingham 2000, Berggren 2001). High transient population growth rate may enhance the probability of population establishment.…”
Section: Discussionmentioning
confidence: 64%
“…A low probability of establishment when population size is small is consistent with the low success rate in establishing biocontrol agents (Grevstad 1999, Stiling 1990, Shea and Possingham 2000, Berggren 2001). High transient population growth rate may enhance the probability of population establishment.…”
Section: Discussionmentioning
confidence: 64%
“…For example, both Burkey (1997) and Belovsky et al (1999) found that time to extinction did not depend on initial population size, yet a nearly universal prediction of theory is that population persistence should increase monotonically with initial population size, and field experimental introductions of garlic mustard Alliaria petiolata (Drayton & Primack 1999), bush-crickets Metrioptera roeseli (Berggren 2001), and two species of beetles (Galerucella calmariensis and G. pusilla) (Grevstad 1999) all found lower extinction risk in larger introduced populations. The study systems used by Burkey (1997) and Belovsky et al (1999) (protists and Artemia, respectively) both have high reproductive capacities, and under benign conditions such as those used in their laboratory experiments, low numbers of individuals may be expected to increase rapidly.…”
Section: K N O W L E D G E G a P Smentioning
confidence: 99%
“…However, confirming links between observed extinctions and theory is complicated by the complexity of natural systems, where populations exist within a network of interacting species, are distributed patchily over a heterogeneous space, and are subject to a range of environmental conditions. In field studies, isolating populations from such confounding factors is often impossible or logistically prohibitive (but see Berggren 2001;Drayton & Primack 1999;Grevstad 1999 for examples of successful field studies). Laboratory tests of extinction theory present a feasible alternative by providing a simplified, tractable system where exogenous factors can be eliminated, and targeted mechanisms can be controlled, replicated and manipulated (Lawton 1995;Daehler & Strong 1996;Benton et al .…”
Section: Introductionmentioning
confidence: 99%
“…These populations were introduced as a part of a large-scale introduction experiment in 1994 and 1995 (for more details see [12,13]). At the time of collection, the bush-crickets had been in their adult form for approximately 2 months.…”
Section: Study Species and Populationmentioning
confidence: 99%
“…Populations were introduced to 70 locations with varying propagule sizes and landscape variables to study the effects of these factors on population establishment and persistence [12,13]. Since then, these populations have been regularly monitored and show that propagule size and habitat connectivity affect population persistence and growth [12,14], and that patch size and connectivity are correlated with immune response and FA [13,15]. Because these relationships may be, at least in part, related to genetic diversity in isolated populations [13,15], the landscape and population history factors which may confound relationships between immune response and FA need to be accounted for.…”
Section: Open Accessmentioning
confidence: 99%